A search for cortical correlates of trait impulsivity in Parkinson´s disease - Kubera, Katharina Maria; Schmitgen, Mike; Nagel, Simon; Hess, Klaus; Herweh, Christian; Hirjak, Dusan; Wolf, Robert Christian (Behavioural brain research, 2019)
BACKGROUND: Impulsivity is an enduring personality trait that is highly relevant for the development of neuropsychiatric disorders. Although impulse control disorders (ICD) are well-characterized non-motor features in Parkinson's disease (PD), mainly related to medication, little is known about neural correlates reflecting trait aspects of impulsivity in PD patients. Here, we address the question whether motor, attentional and non-planning components, measured by the Barratt Impulsiveness Scale (BIS-11), are distinctly related to cortical thickness and cortical folding abnormalities in PD when compared to age-matched healthy controls (HC). - METHOD: We investigated cortical thickness (CT) and complexity of cortical folding (CCF) in 22 PD patients with moderately advanced disease stages without ICD and 18 HC using high-resolution structural magnetic resonance imaging (MRI) data. Surface-based data analysis was driven by CAT12 toolbox. - RESULTS: PD patients showed widespread CT loss in frontal, cingulate, temporo-parietal and occipital regions (FDR corrected at p < 0.05 using threshold-free cluster enhancement). Significant differences in CCF between groups were not found. Using a multiple regression model, CT in inferior and superior frontal, anterior cingulate and precentral regions significantly predicted BIS attentional subscores (p = 0.041). - CONCLUSION: These data suggest a specific cortical trajectory associated with impulsivity in moderately advanced staged PD patients. The attentional dimension of trait impulsivity appears to be specifically related to CT, in contrast to alterations of early neurodevelopmental markers, i. e. CCF. Our results shed light on structural correlates of trait impulsivity in PD patients and establish a baseline for future research into neural risk factors potentially predisposing to ICD development.
Gesehen am 12.07.2019